Ansiedad social y su influencia en el sistema familiar de una adolescente de 18 años - Peña Zapata, Lady Tatiana (2020)
This case study has as topic: social anxiety and its influence on the family system of an adolescent and as objective to demonstrate how social anxiety influences the family system. For the elaboration of the diagnosis, several instruments of psychodiagnostic evaluation were used, being these the following: clinical history, the Liebowitz social anxiety scale test (LSAS) and the Self-esteem scale test. The analysis of the same one could corroborate to demonstrate that this problem of anxiety if it has influence in the familiar system. Within the case, it was possible to evidence that the affected areas were the affective and the social-behavioral, due to this, it was proceeded to apply the appropriate techniques as cognitive-behavioral techniques which were directed to the improvement of the patient according to the required aspects. Once the treatment was completed, it was possible to evidence the significant improvement in the emotional state, such as self-esteem and the reduction of the symptoms of social anxiety suffered by the patient, thus improving her interpersonal relations both with the community and with her family.